Enhancement of mechanical properties of ceria-calcia stabilized zirconia by alumina reinforcement. Issue 11 (September 2020) - Tovar-Vargas, D.; Turon-Vinas, M.; Anglada, M.; Jimenez-Pique, E.
Abstract: Zirconia ceramics stabilized using 10 mol% CeO2 and 1 mol% CaO were studied with the addition of small amounts of α-alumina. The elaboration process of five different compositions was done by wet mixing of powders using 0, 2.5, 5, 10, and 15 wt% alumina, followed by pressing and sintering. The 2.5 wt% alumina addition reduced the grain size, which led to an increase in hardness and the 10 wt% alumina samples showed the maximum mechanical strength (around 1000 GPa), measured by the ball on three balls bending test. The fraction of monoclinic phase around Vickers indentations is reduced by the presence of alumina, but the transformability and resistance to cracking by Vickers indentations are still much higher than for 3Y-TZP. The hydrothermal degradation resistance was also improved by the addition of alumina, with only a very small increase of monoclinic phase of about 1 % in volume after aging for 30 h in standard autoclaved conditions. The enhancement in mechanical properties and LTD resistance leads the path to explore the use of these materials in biomedical applications.